Knockdown resistance (kdr)-associated organochlorine resistance in mosquito-borne diseases (Culex pipiens): A systematic review and meta-analysis - Ebrahim Abbasi; Salman Daliri; Asghar Talbalaghi; Fatemeh Mehrpouya; Maryam Hasanzadeh arab; Atena Aslvaeli; Mohammad Djaefar Moemenbellah-Fard (Heliyon)
Background: Culex pipiens is the vector of a large number of pathogens in humans. Use of insecticides to deal with this vector is the most important way to controlling it. However, in recent decades, resistance to insecticides has been reported in this vector. One of the main insecticides used to fight this vector is organochlorine insecticides. Accordingly, this study was conducted to investigate the prevalence of Knockdown resistance (kdr) in Culex pipiens against organochlorine insecticides. Methods: This study was conducted via systematic review and meta-analysis approach in the field of kdr prevalence in Culex pipiens against organochlorine insecticides. Accordingly, during the search in the scientific databases PubMed, Web of Science, Biooan.org, Embase, ProQuest, Scopus, and Google Scholar without time limit until the end of November 2023, all related articles were extracted and analyzed. The statistical analysis of the data was performed using random and fixed effects model in the meta-analysis, Cochran's test, I2 index, and meta-regression by STATA software version 17. Results: seven studies with a sample size of 2029 Culex pipiens were included in the meta-analysis process. Based on the findings, the kdr resistance prevalence against Deltamethrin, Malathion, Permethrin, and DDT insecticides was estimated as 30.6 %, 42 %, 17.9 %, and 76.3 % respectively. Among them, the highest resistance was observed to DDT and the lowest to Permethrin. Conclusion: Based on the findings, a large proportion of Culex pipiens mosquitoes were resistant to DDT insecticide. However, this vector was highly sensitive to Deltamethrin, Malathion, and Permethrin insecticides. Given the different resistance ratios in different regions of the world, it is recommended to conduct studies on the prevalence of kdr in Culex pipiens.